The consensus in Islamic jurisprudence: towards reviving and applying the concept in the contemporary societies - Moustapha, Sano Koutoub (s.n, 2012)
This study elaborated on the concept of consensus (Ijma) in Islamic jurisprudence, its history, jurisprudential role, social and practical contribution to solving general problems and crisis in Muslim societies. The study also highlighted the vital role of 'Ijma in inspiring and maintaining social order during the Prophetic and Khalifat eras. Yet, the study discussed the impact of confrontation relationship between scholars and rulers in Islamic history on the concept of Ijma. In this context, the study proposed ways and means of reviving and reactivating the role of this concept in handling general and critical issues in the Muslim societies